Free-Space Optical Communication Using Coherent Detection and Double Adaptive Detection Thresholds - Lin Li; Tianwen Geng; Ye Wang; Xueliang Li; Jiabin Wu; Yatian Li; Shuang Ma; Shijie Gao; Zhiyong Wu (IEEE Photonics Journal, 2019)
In this paper, on–off Keying free-space optical (FSO) communication with coherent detection and double adaptive detection thresholds is proposed. The 3-bit encoding and double adaptive detection thresholds presented in the scheme can significantly improve the system performance, and there is no need of acquiring the instantaneous channel state information and probability density function (pdf) of the turbulence model. In order to enhance the accuracy of the threshold even further, the decision-aided method is offered to set the second detection threshold. The pdfs of the detection thresholds and the average bit error rate (BER) of the system are theoretically derived. Numerical studies show that the performance of the system is comparable to the performance of the idealized adaptive detection system and the loss of the signal-to-noise ratio (SNR) performance is only 1 dB at a BER of 10−9 over a lognormal turbulence channel with normalized standard deviation of irradiance σ = 0.25 and phase noise with normalized variance $σ _{φ}^2 = 0.07$ . Hence, this scheme can contribute to the performance improvement of the FSO system and its practical realization.